Exploring The Influencing Factors of Dietary Transition Towards Vegetarianism in Korea's Southern Provinces - Njoku, Okechukwu Enyeribe; Ok, Kim Hyun; Gon, Kim Gwi; Yulianti, Ni Made Dhian Rani (Jurnal Ilmiah Manajemen & Bisnis, 2024)
This study examines the determinants that impact consumer decision-making in relation to vegetarian diets in several regions of South Korean provinces. The study investigates the relationship between vegetarianism (dependent variable) and many explanatory variables, including ethical-animal welfare, health, environment, social issues, mood-emotion, and religious beliefs. Logistic regression analysis was conducted using Likert scale data collected from 264 respondents. The findings indicate that health, ethical considerations regarding animal welfare, and environmental concerns are important factors that influence the choice to adopt a vegetarian diet. It suggests that overseas students in Korea are increasingly conscious of and interested in health, ethical, and sustainable dietary options. Furthermore, the selection of a vegetarian diet is significantly influenced by health considerations, suggesting that persons who prioritise their well-being are more likely to adopt a vegetarian lifestyle. Religious views, emotion, and gender exert different levels of effect on the choice to adopt a vegetarian diet. The results of this study have consequences for how consumers behave, as well as for marketing managers and decision-makers. Businesses in the food business, especially, can gain advantages by catering to the demands and preferences of consumers who prioritise ethical and animal welfare principles, as well as those who value health and environmental sustainability. Implementing and promoting vegetarian and vegan choices in nearby eateries can efficiently appeal to and cater to this particular target audience.